The Interaction of Spinach Nitrite Reductase with Ferredoxin: A Site-Directed Mutation Study - Hirasawa, Masakazu (Oxford University Press, 2009)
A series of site-directed mutants of the ferredoxin-dependent spinach nitrite reductase has been characterized and several amino acids have been identified that appear to be involved in the interaction of the enzyme with ferredoxin. In a complementary study, binding constants to nitrite reductase and steady-state kinetic parameters of site-directed mutants of ferredoxin were determined in an attempt to identify ferredoxin amino acids involved in the interaction with nitrite reductase. The results have been interpreted in terms of an in-silico docking model for the 1:1 complex of ferredoxin with nitrite reductase.